Single-cell and spatial transcriptome analyses reveal tumor heterogeneity and immune remodeling involved in pituitary neuroendocrine tumor progression - Wan Su; Zhang Ye; Jifang Liu; Kan Deng; Jinghua Liu; Huijuan Zhu; Lian Duan; Chen Shi; Linjie Wang; Yuxing Zhao; Fengying Gong; Yi Zhang; et al. (Nature Communications)
Abstract Pituitary neuroendocrine tumors (PitNETs) can be invasive or aggressive, yet the mechanisms behind these behaviors remain poorly understood, impeding treatment advancements. Here, we integrat single-cell RNA sequencing and spatial transcriptomics, analyzing over 177,000 cells and 35,000 spots across 57 tissue samples. This comprehensive approach facilitates the identification of PitNETs tumor populations and characterizes the reconfiguration of the tumor microenvironment (TME) as PitNETs progress and invade. We trace the trajectory of TPIT-lineage PitNETs and identify an aggressive tumor cluster marked by elevated p53-mediated proliferation and a higher Trouillas classification, both associated with tumor progression. Additionally, we document the heterogeneity of immune stromal cells within PitNETs, particularly noting the enrichment of SPP1+ tumor associated macrophages (TAMs) in invasive tumors. These TAMs facilitate tumor invasion through the SPP1-ITGAV/ITGB1 signaling pathway. Our in-depth single-cell and spatial analysis of PitNETs uncovers the molecular dynamics within the TME, suggesting potential targets for therapeutic intervention.